Different degradation mechanisms of carbamazepine and diclofenac by single-atom Barium embedded g-C3N4: the role of photosensitation-like mechanism - Jialiang Liang; Wei Zhang; Zhiwei Zhao; Liu, Wen; Jiangyu Ye; Meiping Tong; Yunyi Li (Journal of Hazardous Materials, 2021)
This study reports the different degradation mechanisms of carbamazepine (CBZ) and diclofenac (DCF) by single-atom Barium (Ba) embedded g-C3N4. Single-atom Ba is anchored onto g-C3N4 by forming ionic bond with triazine ring, thus greatly enhances the photocatalytic activity with an atom ratio of 1.78%. CBZ undergoes a typical photocatalysis mechanism, while DCF is degraded via a photosensitization-like process, which does not need band gap excitation of photocatalyst. By means of Density Functional Theory (DFT) calculation, the selectivity is found to be related with the different valence excitation modes of CBZ and DCF. Specifically, CBZ undergoes a local excitation, which does not obviously affect molecular configuration. In contrast, DCF undergoes a charge transfer excitation, which significantly changes the reactive sites distribution and facilitates photosensitization-like degradation. Due to the different degradation mechanism, the effects of pH, co-existed anions, and water matrix are also different. Since photosensitization-like mechanism does not rely on photo-generated holes mediated oxidation, the degradation efficient of DCF shows higher anti-interference capacity in real water.
Keywords: First excited state; Graphitic carbon nitride; Photosensitation-like; Single-atom Barium; Valence excitation mode